Kinematic control based on dual quaternion algebra and its application to robot manipulators - Figueredo, Luis Felipe da Cruz (2016)
Tese (doutorado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2016.